The perception of community on coastal erosion issue in Selangor, Malaysia - Asmawi, M. Zainora; Ibrahim, Ainaa Nawarrah (IACSIT Press, 2013)
Malaysia is a maritime nation blessed with invaluable coastlines. Hence it is important to preserve its precious coastal areas in a sustainable manner. However, coastal areas are continuously facing tremendous development pressures both from natural and anthropogenic factors. These include tsunami event, rapid urbanization process, aquaculture sector, oil and others. Consequently these situations create problems to coastal areas. For instance, the issues of erosion nand loss of habitats are significant in many maritime nations. Thus, this research was initiated by the global phenomenon on coastal areas, particularly erosion problem. The research addresses the issue of coastal erosion as one of the key coastal problems in Selangor. The coastlines of Selangor were selected as it experienced erosion problem relatively significant due to continuous development growth. The objectives of the research were: to comprehend the perception of the coastal community in relation to the issue of coastal erosion in Selangor; to analyze the causal factors contributing to coastal erosion in Selangor;and to analyze the severity of coastal erosion issues in Selangor. Research methods applied was mainly by conducting questionnaire survey to a total of 377 coastal residents and site-observation. This analysis demonstrates that Selangor is currently experiencing severe erosion problems at some stretches of its coastlines, which were considered as Rank 1 (extremely dangerous). These areas involved 33 km of coastal areas. Among the areas are Bagan Beting, Sungai Besar, Bagan Sekinchan, Jeram and Sungai Sembilang. Results from questionnaire survey also indicated that coastal erosion was significant in Selangor with 77% of respondents agreed to that statement. In addition, 75% of them felt that their coastlines were considered as seriously affected’. Overall, this research managed to achieve its outlined objectives.